Concretos refratários espinelizados : projeto da microestrutura e análise da corrosão - Sako, Eric Yoshimitsu (2013)
The addition of magnesium-aluminate spinel (MgAl2O4) in refractories for secondary steel refining has been considered for years one of the more feasible alternatives to reduce the corrosive wear imposed by the aggressive steel ladle environment. Nonetheless, the corrosion resistance of spinel refractory castables is still not fully understood, mainly regarding to the influence of chemical and microstructural characteristics of such materials. This aspect is basically related to: 1) the limited knowledge on the castable microstructural evolution with temperature and, 2) the usual evaluation of commercial products with unknown compositions. In order to overcome this drawback, the main objective of the present project is to understand the microstructural behavior of spinel refractories during sintering and, as a consequence, how the generated microstructure interacts with basic slags at high temperatures. The slag penetration into these materials was clearly associated not only with the sort of incorporated spinel (pre-formed or in situ), but mainly to the previous location of crystals of an additional phase, the calcium hexaluminate (CaO.Al2O3 - CA6) one. When present at the border of the aggregates, CA6 grains provide a suitable protection of the castable structure during the interaction with molten slag, suppressing further infiltrations. Additionally, materials with reduced apparent porosity and average pore size also presented high corrosion resistance. Based on this information, high performance refractories were obtained by a better raw materials selection procedure. The colloidal alumina addition, for instance, resulted in a microstructure with favorable physical aspects, whereas the presence of in situ spinel led to CA6 further generation at target locations. The attained results disclose novel opportunities to produce refractory castable with excellent corrosion resistance, which may reduce the failures rate during operation and increase the steel ladle productivity.